2005
DOI: 10.1111/j.1365-2222.2005.02336.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term exposure to background air pollution related to respiratory and allergic health in schoolchildren

Abstract: A moderate increase in long-term exposure to background ambient air pollution was associated with an increased prevalence of respiratory and atopic indicators in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
98
2
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(113 citation statements)
references
References 47 publications
10
98
2
3
Order By: Relevance
“…Concentration levels vary greatly depending on the time of day, season and place of measurement, especially for inhalable particulates (<PM 10 ) PM₁₀ is associated with increased mortality and morbidity in many cities worldwide and the risk is greatly pronounced among susceptible populations, including the elderly, children, and people with pre-existing health conditions [7]. Penard-Morand et al [8] carried out a large population-based study of children from 108 randomly selected schools in 6 French cities, elevated concentrations of PM 10 was significantly associated with an increased risk of suffering from allergic rhinitis, past year rhinoconjunctivitis and wheeze.…”
Section: Introductionmentioning
confidence: 99%
“…Concentration levels vary greatly depending on the time of day, season and place of measurement, especially for inhalable particulates (<PM 10 ) PM₁₀ is associated with increased mortality and morbidity in many cities worldwide and the risk is greatly pronounced among susceptible populations, including the elderly, children, and people with pre-existing health conditions [7]. Penard-Morand et al [8] carried out a large population-based study of children from 108 randomly selected schools in 6 French cities, elevated concentrations of PM 10 was significantly associated with an increased risk of suffering from allergic rhinitis, past year rhinoconjunctivitis and wheeze.…”
Section: Introductionmentioning
confidence: 99%
“…Aunque algunos estudios reportan que no hay cambios en la prevalencia de síntomas respiratorios y asma con la disminución de concentraciones de PM 10 36 , otros estudios muestran un mayor efecto de este contaminante en pacientes asmáticos 37,38 .…”
Section: Discussionunclassified
“…For adult male and female patients, the total weight of the chemical variables in the occurrence of asthma ER visits is higher in the pollen season of Ambrosia compared to the pollen-free season (Table 2). Some studies found that exposure to outdoor air pollutants may increase the risk of allergic airway diseases [11,[55][56][57][58]. This may be explained by the fact that air pollutants, especially burning of fossil fuels, can affect allergens.…”
Section: Discussionmentioning
confidence: 99%
“…Weather conditions can also affect both the biological and chemical air pollutants. There are evidences on the effect of air pollution upon allergens, increasing exposure to the latter, their concentration and/or biological allergenic activity [11][12][13]. Habitats and levels of pollen are changing in Europe, as a result of cultural factors, more international travel and climate change [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%